Spionageabwehr und Sabotageschutz - Gärditz, Klaus Ferdinand; Dietrich, Jan-Hendrik (Mohr Siebeck, 2025)
Counterspionage is caught between legal requirements, challenging official cooperation and security policy constraints. The authors of this volume analyze powers, regulatory gaps and institutional structures in order to systematically shed light on current challenges and reform approaches.
PublicationDate: 20250516
Keywords: Gefahrenabwehr -- Sicherheitspolitik -- staatliche Sicherheit -- Nachrichtendienst -- individuelle Grundrechte -- Sicherheits- und Bedrohungslagen -- Verfassungsrecht und Staatslehre -- Besonderes Verwaltungsrecht -- Völkerrecht